Keeping your coparent in mind: A longitudinal investigation of mindfulness in the family system. Issue 2 (5th August 2021) - DiMarzio, Karissa; Peisch, Virginia; Acosta, Juliana; Dale, Chelsea; Gutierrez, Jennifer; Parent, Justin
Abstract: Recent studies have increasingly focused on mindfulness as it relates to interpersonal processes. In particular, cross‐sectional research has shown that parents' dispositional mindfulness is associated with increased mindful parenting and coparenting, as well as improved coparenting relationship quality. The current study replicates and extends such work, representing the first longitudinal investigation of mindful coparenting. A sample of 449 parents (60% mothers) of children between the ages of 3 and 17 years were recruited online through Amazon's Mechanical Turk (MTurk) as part of a larger study on the assessment of parenting. Parents reported on their dispositional mindfulness, mindful coparenting, and coparenting relationship quality at three time points across an 8‐month period. Results from a cross‐lagged panel model using maximum likelihood estimation suggested that higher levels of parental mindfulness at baseline were related with higher levels of mindful coparenting at 4 months, which, in turn, were related to higher quality coparenting relationship at 8 months. Support for this model was found for both mothers and fathers and across all examined child age groups (i.e., early childhood, middle childhood, and adolescence), highlighting the robust nature of these effects. Overall, findings suggest that increasing mindfulness at an individual level can promote meaningful change within a family system, specifically through improvements in coparenting and parent–child interactions. Resumen: Los estudios recientes se han centrado cada vez más en la conciencia plena en relación con los procesos interpersonales. En particular, las investigaciones transversales han demostrado que la conciencia plena disposicional de los padres está asociada con una crianza y una cocrianza más conscientes, así como con una mejor calidad de la relación de cocrianza. El presente estudio reproduce y amplía dicho trabajo, y representa la primera investigación longitudinal de cocrianza consciente. Se reunió virtualmente una muestra de 449 padres (el 60 % madres) de niños de entre 3 y 17 años mediante Amazon's Mechanical Turk (MTurk) como parte de un estudio más extenso sobre la evaluación de la crianza. Los padres informaron sobre su conciencia plena disposicional, la cocrianza consciente y la calidad de la relación de cocrianza en tres intervalos de tiempo durante un periodo de ocho meses. Los resultados de un modelo de panel de retardo cruzado utilizando la estimación por máxima verosimilitud indicaron que los niveles más altos de conciencia plena de los padres en el momento basal estuvieron relacionados con niveles más altos de cocrianza consciente a los cuatro meses, los cuales, a su vez, estuvieron relacionados con una relación de cocrianza de mayor calidad a los ocho meses. Se encontró respaldo para este modelo tanto en el caso de las madres como en el de los padres y entre todos los grupos etarios de los niños analizados (p. ej.: primera infancia, segunda infancia, adolescencia). Asimismo, se destacó la índole sólida de estos efectos. En general, los resultados indican que aumentar la conciencia plena a nivel individual puede promover un cambio significativo dentro de un sistema familiar, específicamente mediante mejoras en la cocrianza y en las interacciones entre padres e hijos. 摘要: 最近的研究越来越关注正念觉知，因为它与人际交往过程有关。特别是，横断面研究表明父母之习惯性正念与提升了的正念育儿和抚养关系，以及与改善了的共同养育关系质量有关。本研究复制和扩展了这类研究，代表了第一个有觉知的共同抚养情境的长期性研究。通过亚马逊的"土耳其机器人"(MTurk)在网上招募了449名家长(60%为母亲)，家有3岁至17岁孩子，本研究是有关育儿能力评估的一个更大规模的研究中的一部分。父母在8个月内的三个时间节点都要报告三项具体内容的情况：习惯性的正念，有觉知的抚养方式和共同抚养关系的质量。使用最大可能性估算的交叉滞后模型的结果显示，在基线的父母之觉知水平越高，在4个月时父母的共同养育觉知水平就越高，而这反过来又与8个月时更高质量的共同抚养关系相关。该模型在母亲和父亲以及所有受调查儿童年龄组(即幼儿期、中期、青春期)中都得到了支持，突显了这些影响的强大性质。总体而言，研究结果表明，增加个人层面的觉知意识可以促进家庭系统内的有意义的变化，特别是通过改善共同养育孩子和亲子互动。